Evaluation of Soil Quality Status under Different Forest Tree Species in Nigeria - AKANBI, Olorunfemi Sunday Ojo; Olufisayo , Onawumi Adeyinka; Edibo, Gabriel Ojodale (Transactions on Engineering and Computing Sciences, 2021)
A study was carried out at Forestry Research Institute of Nigeria, Ibadan, South -western, Nigeria in the second quarters of 2018 to evaluate the current status and the distribution of some soil quality factors of study area. The study also aimed at suggesting strategies for efficient management of the soil quality factors in the study areas. Soil samples were collected under six (6) different forest trees species plantations. The samples were subjected to routine laboratory analytical protocol for the determination of both physical and chemical properties of the samples. Results implicated that the soil organic matter (SOM) of the study area varied from one forest plantation to the other. However, SOM was found to be highest under natural forest (NF) with a mean value of 3.90% while open field had the least with a mean value of 1.62%. Similar results were observed for soil total nitrogen (N). There was a significant (p<0.05)difference in the amount of exchangeable K contents (0.008cmol/kg) in soils under open field with less ground cover and forest tree species relative to soils under NF, Nauclea dideirichi (ND) and Mangifera indica (MI) respectively. Soils under NF significantly recorded the highest exchangeable Ca compared to open field and others. It can therefore be concluded that good agricultural management practises that will enhance soil quality factors and multi forest species cultivation be encouraged for effective and efficient nutrient management systems in the forest ecosystems for enhancement of bio diversities of both micro and macro organisms. However, due to population pressure on the available land for other non-agricultural purposes coupled with annual bush burning, inadequate rainfall, lack of good agricultural practices and non-availability of natural forest for farming, it has become imperative that agroforestry system of farming in which trees or shrubs are grown in association with crops is advocated.